PANCASILA SEBAGAI LANDASAN DASAR MEMBENTUK KARAKTER DALAM ETIKA BERLALU LINTAS MELALUI MATA PELAJARAN IPS - Sari, Fitria (Dharmas Education Journal (DE_Journal), 2023)
The lack of awareness of the younger generation in traffic is something that needs to be a concern for all of us, this can be seen from the data on the high rate of traffic violations and the high number of road accidents. Based on data sources from the Republic of Indonesia police in 2021, there have been 5,350.00 accidents and for traffic violators data in 2021 as many as 29,615.00. Case. This indicates that the public's awareness of traffic ethics is low so that it is not only dangerous for themselves but can also harm others as other road users. This article examines Pancasila as the basic foundation for shaping character in traffic ethics through social studies subjects. Social studies learning emphasizes how to shape the character of students who are implanted in the educational process at school. Through these social studies subjects, students are instilled values ​​and norms that must be a reference in behavior, so that they will form good ethics. Ethics in life includes ethics in traffic, so social studies learning is instilled in how to form good character based on Pancasila. Pancasila is the basic foundation in shaping behavior in accordance with the values ​​that become a reference in life, both in the form of divine values, human values, values ​​of unity, populist values ​​and social values. These values ​​are used as benchmarks and references in behavior, so that they are in line with the goal of social studies learning, which is to make students good citizens.